Strengthening the state institutional communication development system for radicalism management in Indonesia - Sazali, Hasan (Faculty of Communications Science, Dr. Soetomo University, 2022)
This paper aims to analyse the rise of radicalism in Indonesia which is at an alarming stage. It needs to be watched out by various parties, especially the government as a policymaker. It is necessary to strengthen communication systems to develop state institutions to overcome radicalism. This paper results from research using descriptive-analytical methods with qualitative approaches and case studies. As a result, in tackling radicalism in Indonesia, State Institutions have synergised but not yet optimally. This is because there are still differences in perceptions between institutions assessing radicalism. Therefore, there needs to be particular terminology, such as the National Strategic Plan, which is made to equalise the perception so that all state institutions can work optimally in tackling radicalism. With the development of the Strategic Plan, state institutions will automatically synergise with all levels of society so that the handling of radicalism can be quickly prevented.